Cutaneous Lupus Erythematosus Patients With a Negative Antinuclear Antibody Meeting the American College of Rheumatology and/or Systemic Lupus International Collaborating Clinics Criteria for Systemic Lupus Erythematosus. Issue 11 (29th October 2019) - Tarazi, Meera; Gaffney, Rebecca G.; Kushner, Carolyn J.; Chakka, Srita; Werth, Victoria P.
Abstract : Objective: Systemic lupus erythematosus (SLE) is a disorder that is heterogeneous and can be difficult to diagnose. One hallmark of the disease is the presence of antinuclear antibodies (ANAs), a feature that has been incorporated into multiple classification criteria over the years. In this study, we used a database of patients with cutaneous lupus erythematosus (CLE) to determine how many had a negative ANA and met criteria for SLE using the American College of Rheumatology (ACR) and/or Systemic Lupus International Collaborating Clinics (SLICC) criteria. Methods: We used a database of 301 biopsy‐proven CLE patients that contained information including ANA status and the presence of features of SLE. The database was searched for patients who had a negative ANA result and whether or not they met SLE criteria using the ACR and/or SLICC criteria. Results: Of the 301 patients with biopsy‐proven CLE and a known ANA, 111 had a negative ANA test (36.9%) and 27 had an ANA test that fluctuated (33.3%). In all, 20 ANA‐negative patients met SLE criteria (18.0%), and 12 patients with a fluctuating ANA test met SLE criteria (44.4%). Of all patients who had either a negative or fluctuating ANA result and who met criteria for SLE (n = 32), 27 patients had involvement of ≥1 organ system other than skin (84.4%), and 13 patients had involvement of ≥2 organ systems other than skin (40.6%). Conclusion: Our results show that an ANA is not always present in patients with systemic disease. This fact should be taken into consideration when devising SLE classification criteria to be used for clinical trials.